Technical-Tactical Behaviors Analysis of Male and Female Judo Cadets’ Combats - Miarka, Bianca; Pérez, Diego Ignácio Valenzuela; Aedo-Muñoz, Esteban; da Costa, Lucas Oliveira Fernandes; Brito, Ciro José (Frontiers in Psychology, 2020)
This brief research report showed technical-tactical behaviors of male and female judo cadets during combats, comparing the frequency and time of judo combat actions, techniques and penalties. The data was composed for 3,240 sequential technical-tactical behavior analysis from 108 female and 300 male cadet combats recorded of public judo championships. Combat, standing combat moments, approach action, gripping action, attack, groundwork actions and pause moment were observed and determinant technical-tactical behaviors (frequencies of actions, penalties and type of attacks) analysis were done with FRAMI software, followed by Mann-Whitney and Student’s t-test, p ≤ 0.05. Our main results indicated that male cadets with 58.66s ± 50.26s demonstrated longer gripping action than female with 38.44s ± 30.44s, as standing combat (tachi-waza) had differences between male with 96.8s ± 72s and female athletes with 75.85s ± 56.97s. Moreover, male cadets had higher sacrifice techniques (sutemi-waza) actions than female athletes. This information could be used to a best performance associated with “psyching-up” as much as it could be used on physical training and technical-tactical ability of female and male cadets.